SALURAN DISTRIBUSI KOMODITI CABAI RAWIT DI PASAR BERSEHATI KOTA MANADO - Heryanto ., Siahaan; Lyndon R. J. Pangemanan; Audrey J. M. Maweikere (AGRI-SOSIOEKONOMI, 2018)
This study aims to find out the distribution channel of Cayenne Chili at Bersehati Market, Manado City. The data used are primary data. Primary data is obtained through a list of questions. Sampling method by purposive sampling and Snowball Sampling method for marketing institution, the sample is obtained based on information from interview to the respondent and traced to the next respondents in chains. The number of respondent is 20 people because it is representative of respondent. The results of this study show that the Distribution Channel that occurs in Bersehati Market consists of 3 distribution channels. Marketing institutions involved include collecting dealers, wholesalers, retailers. Distribution activities in Bersehati Market are activities that start from partners and cooperation between farmers and marketing institutions involved in marketing activities of cayenne pepper.*lwths*.